Technology, Trust, and Religion Roles of Religions in Controversies on Ecology and the Modification of Life - Drees, Willem (LUP Academic, 2009)
What does it mean to be human in a world of technology? What could be the role of religion in responding to the ecological crisis? Should we be concerned about the modification of food, and even of ourselves? Who do we trust to make decisions regarding our common future? What do we use our technology for? These are not questions for experts only. How can the wider public be involved? Do experts and the general public trust each other sufficiently? Or is the public ignorant, in the eyes of the scientists? And are too many engineers narrow minded, according to the general public? The contributors to this timely and necessary volume address expertise, trust and engagement, as we consider our technological condition , religious resources for the ecological crisis , biotechnology , and matters of trust between scientists and the general public. With contributions from leading scholars in the field, including James Miller from Queen's University, Canada and Tony Watling from the University College, London, this book will captivate a range of readers interested in the spirtitual dimension of of our culture and society.